BUILDING THE AIR DEFENSE COVERT INFORMATION AND MEASURING SYSTEM BASED ON ORTHOGONAL CHAOTIC SIGNALS - Kostantiv Vasyuta; Fedor Zots; Irina Zakharchenko (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the paper is a covert information and measuring system based on orthogonal chaotic signals. The goal of the work is to synthesize a covert information measuring system built on the basis of orthogonal chaotic signals. The tasks to be solved included assessing the potential for organizing multi-channel capacity using chaotic carriers; studying the ways of application of chaotic signals in the wireless systems of data transmission; synthesizing the general structure of МIMO radar system based on the orthogonality of chaotic signals. General scientific and special research methods were used while conducting the research, in particular, the system analysis and mathematic modelling. The following results were obtained. The concept of building a net-centric multi-radar information measuring system (MIMS) on the basis of the specific properties of chaotic signals (processes) is proposed in the paper. It is shown that the use of orthogonal chaotic signals for detecting air targets and transmitting information about them increases noise immunity, resolution characteristics and transmission capacity; enables providing electromagnetic compatibility and separating information-detecting and transmitting channels. MIMS block diagram is synthesized. Conclusions. Specific properties of chaotic signals make it possible to apply them to build data transmissions systems according to the MIMO principle and multichannel radars. Based on chaotic signals, a multiradar information measuring system can be built. The above techniques can be implemented to build a network of unattended radars as well as in multichannel communication systems. They can be applied to control air traffic and can be used in the air defence net-centered systems to create common covert information and telecommunication space.